Chemical composition and antibacterial activities of essential oil of Thymus capitatus from Jordan - Qaralleh, Haitham; Khleifat, Khalid M; Tarawneh, Khaled A; Abboud, Muayad M; Syed Osman Idid, Syed Zahir Idid; Darnis, Deny Susanti; Althunibat, Osama Yousef (2009)
The essential oils from the dried leaves of Thymus capitatus was isolated by steam distillation. The collected oil were analyzed by GC-MS and also evaluated for in vitro antibacterial activity. Twenty-two compounds, constituting about 95.4% of the total oil, were identified. The main constituents were thymol (39.2%), p-cymene (19.4%), carvacrol (11.8%) and g-terpinene (7.4%). The antibacterial activity of the oil was estimated using agar disc diffusion and broth microdilution methods against four bacteria. The essential oils wer found to show a broad spectrum of antibacterial activity against all the tested bacteria strains. Pseudomonas aeruginosa was the most sensitive bacteria. The essential oil were equally active against Gram-negative and ram-positive bacteria